Quantum physics: Spooky action gets collective - Weidemüller, Matthias (Nature, 2013)
Thousands of atoms in a gas can share a single Rydberg excitation. Quantum entanglement between such an excitation and a single photon has now been realized deterministically. See Letter p.466
Gesehen am 18.10.2021